Oestrogen and progesterone receptor distribution in the cancerous breast. - Panahy, C. (1987)
To test the hypothesis that steroid hormone receptor expression is particularly pronounced in breast tumours when compared with non-neoplastic tissue, mastectomy samples were divided into 16 sectors. Multifocal tumours, of varying receptor phenotype were found in 4 patients and in addition different regions of large tumours also showed varying receptor contents. Remaining samples were found to consist of normal tissue, with fat, connective tissue and some benign breast disease. In the 9 patients with oestrogen receptor positive tumours (ER), ER content was invariably much greater in the tumours than in the remainder of the breast. Progesterone receptor (PR) content was not closely related to ER, and was lowest in the poorly differentiated tumours. This relation to differentiation was not seen in ER. The data support the view that ER concentration in ER positive tumours may reflect the transformed nature of neoplastic tissue.